VERBALIZATION OF THE CONCEPT “VATAN” (motherland) BY MEANS OF ENGLISH AND UZBEK PHRASEOLOGICAL UNITS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The author discusses one of the branches of linguistics phraseology, different and contradictory views of linguists on this issue are given with examples. In this article the author examines the verbalization of the " Vatan"(motherland) concept by means of English and Uzbek phraseological units. Outstanding linguists’ points of view concerning this notion are given in this article. The author analyses the English and Uzbek phraseological units and classifies them into 5 groups.